2013
DOI: 10.1111/nmo.12236
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota influence the early postnatal development of the enteric nervous system

Abstract: These findings suggest that early exposure to intestinal bacteria is essential for the postnatal development of the ENS in the mid to distal small intestine. Future studies are needed to investigate the mechanisms by which enteric microbiota interact with the developing ENS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 34 publications
(44 reference statements)
11
185
1
3
Order By: Relevance
“…The effect of microbiota on the formation of neural circuits in the mammalian gut is highlighted by studies of germ-free mice that demonstrated that these animals have altered spontaneous circular muscle contractions and decreased nerve density in the jejunum and ileum (101). In addition, germ-free mice showed reduced sensory neuron excitability, which was corrected following conventionalization with normal microbiota (102).…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 99%
“…The effect of microbiota on the formation of neural circuits in the mammalian gut is highlighted by studies of germ-free mice that demonstrated that these animals have altered spontaneous circular muscle contractions and decreased nerve density in the jejunum and ileum (101). In addition, germ-free mice showed reduced sensory neuron excitability, which was corrected following conventionalization with normal microbiota (102).…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 99%
“…The frequency and amplitude of muscle contractions also were fewer in GF mice. 29 GF mice also differ from conventional mice in the expression of brain-derived neurotrophic factor in the cortex and hippocampus, and synaptophysin and post-synaptic density protein-95 in the striatum, relative to specific pathogen free mice. These quantifiable chemical changes were associated with an exaggerated hypothalamic pituitary stress response (elevation of plasma adrenocorticotropic hormone and corticosterone) in the GF mice.…”
Section: Icrobiome and Neurodevelopmentmentioning
confidence: 99%
“…17 Finally, intestinal bacteria are essential for the postnatal development of the enteric nervous system in the mid-distal SI. 18 The growing awareness of the importance of the gut microbiome in health and disease and recognition of the host-microbe mutualism at the immunological and metabolic levels become crucial for a better understanding of immunopathologies such as autoimmune and inflammatory disorders, allergy and obesity. Microbiome differences between controls and cases have been described for a variety of diseases such as inflammatory bowel disease (both Crohn's disease and ulcerative colitis), obesity, type 2 diabetes, autism and allergies, and involve abnormalities in the relative abundance and representativity of distinct commensal bacteria.…”
Section: Gut Microbiota Health and Diseasesmentioning
confidence: 99%